Nanoimprint crystalithography for organic semiconductors - Shun-Xin Li; Guan-Yao Huang; Hong Xia; Tairan Fu; Xiao-Jie Wang; Xin Zeng; Xinfeng Liu; Yan-Hao Yu; Qi-Dai Chen; Linhan Lin; Hong-Bo Sun (Nature Communications)
Abstract Organic semiconductor crystals (OSCs) offer mechanical flexibility, high carrier mobility, and tunable electronic structures, making them promising for optoelectronic and photonic applications. However, traditional lithographic techniques damage OSCs due to high-energy beams or solvents, leading to high defect densities, poor uniformity, and significant device-to-device variation. Existing methods also struggle to eliminate residual layers while forming independent, complex two-dimensional patterns. A chemical-free nanoimprint crystallography (NICL) method is introduced to overcome these challenges by balancing residual-layer-free nanoimprinting with the fabrication of independent, complex 2D patterns. In situ control of crystallization kinetics via temperature gradient adjustment yields OSC nanostructures with low defect densities and good uniformity. Patterning of various OSCs over a range of feature sizes is demonstrated. The patterned OSCs exhibit good lasing performance and low device-to-device variation (as low as 2%), indicating that NICL is a promising approach for fabricating high-performance, uniform OSC-based devices.